Analisis Korelasi Kepatuhan Hukum K3 Terhadap Produktivitas SDM Melalui Data Kecelakaan Kerja Nasional Portal Satu Data - Mardiman, Mardiman; Taufik, Taufik; Bagaskoro, M Rizal; Rasiwan, Iwan (Indra Institute Research & Publication, 2026)
This study analyzes the correlation between Occupational Safety and Health (OSH) legal compliance and Human Resource (HR) productivity using national workplace accident data from Indonesia's Single Labor Data Portal (2019-2024). A qualitative approach with documentary study design and thematic analysis was employed to identify relational patterns and causal mechanisms, using accident rates as a proxy for OSH compliance. Findings reveal a 152.7% surge in accident cases (from 182,835 to 462,241), indicating systemic enforcement deficiencies. Three causal pathways were identified: (1) reduced workforce capacity due to absenteeism (14-28 days recovery) and permanent disability (6.17% fatality rate); (2) 32% higher motivation and job satisfaction in companies with structured OSH systems; and (3) resource reallocation from accident cost savings (IDR 5-500 million/case) toward HR competency development. Results refute the assumption that OSH is a financial burden, confirming instead that safety investment is a prerequisite for sustainable productivity. Sectoral disparities (construction 29-32%, manufacturing 26%) and severe underreporting (94% in peripheral regions) reflect regulatory gaps, enforcement deficits, and cultural barriers. Policy recommendations include risk-based regulatory reform, digital supervision systems, and OSH integration into vocational curricula to transform compliance from procedural obligation into a strategic productivity driver. The study contributes empirical evidence linking legal compliance with tangible productivity outcomes in Indonesia's labor context.